Period‐Multiplying Cycles at the Transition Between Stick‐Slip and Stable Sliding and Implications for the Parkfield Period‐Doubling Tremors. Issue 7 (8th April 2021) - Mei, Cheng; Barbot, Sylvain; Wu, Wei
Abstract: The recurrence patterns of the Parkfield tremors with period‐multiplying slow and fast ruptures provide new insights on the physics of earthquake cycles. However, the mechanisms behind the peculiar recurrence pattern and the coupling between slow‐slip events and seismic radiations are still unclear. Here, we conduct direct‐shear experiments on polycarbonate and granite fractures under varying stress conditions to investigate the variations of rupture properties near the stability transition. Laboratory slow and fast ruptures sequences produce slip‐predictable period‐multiplying cycles with correlative acoustic energy release, stress drop, event duration, and recurrence intervals. However, gouge accumulation by damage of the granite fracture provokes changes in stiffness and stress drops ratios over multiple cycles, affecting the recurrence intervals and energy release of consecutive slip events. These findings confirm the link between low‐frequency earthquakes and underlying slow‐slip events, with period‐multiplying cycles naturally occurring near the stability transition. Plain Language Summary: The seismic waves of tiny earthquakes are often used to monitor the activity of faults. In particular, tiny tremors that repeat every 3 and 6 days on the San Andreas Fault indicate recurring sequences of slow and fast ruptures. However, how the seismic radiations reflect the rupture characteristics remains unresolved. We perform laboratory direct‐shear experiments on smooth fractures in polycarbonate and granite to explore the spectrum of fracture slip behaviors. We show that as ruptures change from stick‐slip to stable sliding under sequential unloading, sequences of slow and fast ruptures occur near the stability transition. The slip transition is related to effective normal stress and fracture surface roughness. Our data indicate correlative stress drop, recurrence time, and energy release during sequences of slow and fast ruptures, which helps us explain the recurrence pattern of low‐frequency earthquakes on the San Andreas Fault. Key Points: Polycarbonate and granite fractures exhibit period‐multiplying cycles near the stability transition Correlative stress drop, recurrence times, and acoustic energy in slip‐predictable cycles Laboratory data explain the cycle of period‐doubling bursts of low‐frequency earthquakes on the San Andreas Fault